Bridging finance, innovation and sustainability: Inclusive supply chain financing model for Uganda's coffee sector - Roselyn Najjuma; Giuliana Battisti (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
Access to finance is crucial for achieving sustainability goals, especially for poor and developing countries in the global south. However, traditional financial instruments often fall short to support the desired goals. This study explores the potential of a new modality of financing that integrates social, environmental, and economic criteria tailored to the sustainable supply chain finance. We illustrate the case of smallholder coffee farmers in Uganda with very limited collateral; to show how sustainable supply chain financial instruments can help to achieve sustainable goals whilst ensuring fair compensation for farmers and economically viable product for the money lender. Enhancing the welfare of smallholder coffee farmers can significantly strengthen their resilience, allow them to produce in a more environmentally sustainable way and contribute to their broader economic stability. In turn, it would reduce the financial risk to lenders and promote social equity to the benefit of the broader society. The study also explores the partnerships among government, NGOs, and private sector actors in creating supportive ecosystems for sustainable supply chain financing. The analysis underscores the importance of aligning financial incentives with long-term societal goals, advocating for a holistic approach that bridges the gap between profit and purpose.
Keywords: Q14; O13; G23; L81; Q56; 330; Sustainable Supply Chain Finance; financial innovation; coffee value chain; coffee farmers; farmers associations; small holder farmers